2012
DOI: 10.1590/s0104-14282012005000046
|View full text |Cite
|
Sign up to set email alerts
|

Investigação do processo de absorção de água de hidrogéis de polissacarídeo: efeito da carga iônica, presença de sais, concentrações de monômero e polissacarídeo

Abstract: Neste trabalho foi reportada a caracterização de hidrogéis constituídos por metilcelulose (MC) e poliacrilamida (PAAm) preparados pelo processo de reticulação cruzada. As propriedades espectroscópicas e morfológicas foram investigadas por espectroscopia no infravermelho com transformada de Fourier e microscopia eletrônica de varredura, respectivamente. O efeito da carga iônica, presença de sais, concentrações de monômero AAm e polissacarídeo MC na absorção de água e nas propriedades cinéticas dos hidrogéis foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
14
0
3
Order By: Relevance
“…Several authors consider that the Fickian model is not able to describe the complete water absorption behavior of several polymers and/or polymer composites [14][15][16][17] . In fact, in many instances it was found that the Fickian behavior can fit the experimental data points only at the early stages of the absorption process, failing, however, to describe the behavior when the absorption time increases.…”
Section: Non-fickian Behaviormentioning
confidence: 99%
“…Several authors consider that the Fickian model is not able to describe the complete water absorption behavior of several polymers and/or polymer composites [14][15][16][17] . In fact, in many instances it was found that the Fickian behavior can fit the experimental data points only at the early stages of the absorption process, failing, however, to describe the behavior when the absorption time increases.…”
Section: Non-fickian Behaviormentioning
confidence: 99%
“…Some physical factors, such as the presence of hydrophilic groups (-OH, -NH 2 , -COOH, -CONH 2 , -SO 3 H) in the polymer chain structure (laterally or in the main chain), lower crosslink density and high flexibility of the polymer network, can contribute positively to a greater swelling of the material. Bortolin et al (2012) explain that higher concentrations of acrylamide increase the stiffness of the polymer chains, resulting in less water absorption capacity. Generally, polymer networks formed with high AAm concentration are more strongly crosslinked and this reflects in less expansion, causing lower volume of water diffused into the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…O que pode estar relacionado com a quantidade de cargas positivas dispersas na solução de intumescimento, proporcionando uma maior diferença de pressão osmótica entre a solução e a matriz polimérica. 2,38 Tais resultados estão coerentes com os resultados de Q. O comportamento de n e k em função das diferentes soluções salinas e água destilada é representado na Figura 10. Por último, os valores de n e k obtidos em soluções com diferentes valores de pH apresentaram mecanismo de transporte anômalo no limite do transporte Fickiano. Não foi observado variação significativa dos valores de n e k para a faixa de pH estudada.…”
Section: Parâmetros Cinéticosunclassified